Comparative Growth Performance and Nutrient Utilization in Commercial Broiler Chickens fed Diets Supplemented with Herbal Methionine vis-Ã -vis Synthetic DL-Methionine during Summer Season - Tiwari, Devendra Prasad (Indian Journal of Animal Nutrition, 2018)
An experiment was conducted to discern the comparative effects of dietary supplementation of herbal methionine and synthetic DL-methionine on growth performance and nutrient utilization in broiler chicks during summer season. A total of 180, day-old commercial broiler chicks were divided randomly into 6 treatment groups with 3 replicates each and 10 broiler chicks per replicate. There were 6 dietary treatments viz., treatments T1 (control, basal diet without methionine supplementation), T2 (basal diet supplemented with 0.2 % synthetic DL-methionine), T3 (basal diet supplemented with 0.15 % synthetic DL-methionine + 0.05 % herbal methionine), T4 (basal diet supplemented with 0.1% synthetic DL-methionine + 0.1% herbal methionine), T5 (0.05% synthetic DL-methionine + 0.15 % herbal methionine) and T6 (basal diet supplemented with 0.2% herbal methionine). The feeding trial lasted for 42 days viz., 0-21 days (starter phase) and 21-42 days (finisher phase). Weekly body weight and feed intakes were recorded for each treatment group of broiler chicks. A metabolism trial was also conducted during the 6th week of feeding trial. During starter phase (0-21 days) the body weight gains were 576.20, 611.33, 598.13, 606.93, 596.10 and 636.09 g, respectively, in treatment groups T1, T2, T3, T4, T5 and T6 and there was significantly (P<0.05) higher weight gain in broiler chicks of treatment T6 fed basal diet supplemented with 0.2 % herbal methionine than broiler chicks of treatment T1 fed basal control diet only, whereas during finisher phase (21-42 days) there was no significant difference in body weight gain, feed conversion ratio, performance index, protein efficiency ratio and production efficiency factor amongst the various treatment groups of broiler chicks. During starter phase of the study the feed intake was maximum in treatment T4 (971.65 g) and minimum in treatment T2 (932.70 g). The protein efficiency ratio was maximum in treatment T6 (2.85) and minimum in treatment T1 (2.63). The production efficiency factor was also maximum in treatment T6 (2.10) and minimum in treatment T1 (1.76). There was no significant difference in 0-42 days of feeding trial in terms of cumulative average growth performance, body weight gain, feed conversion ratio, performance index, protein efficiency ratio and production efficiency factor amongst the different treatment groups of broiler chicks, however, the feed intake in broiler chicks was maximum in treatment group T3 (3253.93 g) and minimum in treatment group T1 (3056.69 g). The cumulative average body weight gain was recorded lowest (1717.36) in control group T1 and highest (1857.24 g) in fed diet containing 0.2 % herbal methionine T6. It was inferred that the supplementation ofÂ methionine is essential in the diet of broiler chicks to meet the increasing tissue demands associated with growth rate and high production performance in broiler chicks and herbal methionine can replace synthetic DL-methionine in the diet of broiler chicks for growth performance and nutrient utilization.